Outcomes of early carotid stenting and angioplasty in large-vessel anterior circulation strokes treated with mechanical thrombectomy and intravenous thrombolytics. Issue 4 (August 2018) - Mehta, T; Desai, N; Mehta, K; Parikh, R; Male, S; Hussain, M; Ollenschleger, M; Spiegel, G; Grande, A; Ezzeddine, M; Jagadeesan, B; Tummala, R; et al.
Introduction: Proximal cervical internal carotid artery stenosis greater than 50% merits revascularization to mitigate the risk of stroke recurrence among large-vessel anterior circulation strokes undergoing mechanical thrombectomy. Carotid artery stenting necessitates the use of antiplatelets, and there is a theoretical increased risk of hemorrhagic transformation given that such patients may already have received intravenous thrombolytics and have a significant infarct burden. We investigate the outcomes of large-vessel anterior circulation stroke patients treated with intravenous thrombolytics receiving same-day carotid stenting or selective angioplasty compared to no carotid intervention. Materials and methods: The study cohort was obtained from the National (Nationwide) Inpatient Sample database between 2006 and 2014, using International Statistical Classification of Diseases, ninth revision discharge diagnosis and procedure codes. A total of 11, 825 patients with large-vessel anterior circulation stroke treated with intravenous thrombolytic and mechanical thrombectomy on the same day were identified. The study population was subdivided into three subgroups: no carotid intervention, same-day carotid angioplasty without carotid stenting, and same-day carotid stenting. Outcomes were assessed with respect to mortality, significant disability at discharge, hemorrhagic transformation, and requirement of percutaneous endoscopic gastronomy tube placement, prolonged mechanical ventilation, or craniotomy. Results: This study found no statistically significant difference in patient outcomes in those treated with concurrent carotid stenting compared to no carotid intervention in terms of morbidity or mortality. Conclusions: If indicated, it is reasonable to consider concurrent carotid stenting and/or angioplasty for large-vessel anterior circulation stroke patients treated with mechanical thrombectomy who also receive intravenous thrombolytics.